Using impulse to measure intensity during on-water kayaking - de Zee, M; Kristiansen, M.; Lauridsen, H. B.; Klitgaard, K. (VIII Congreso Internacional De Entrenadores De Piragüismo en Aguas Tranquilas, 2022)
BACKGROUND: Mobile power meters in cycling have been around since the 1980's and provide a reliable and valid measure of the cyclists' power output [1]. The cyclists' power output is an objective measure of intensity and is independent of the weather conditions and slope. Moreover, it does not have a time delay like a physiological measure (e.g. heart rate). In cycling, it is relatively straightforward to calculate the power by measuring the torque on the crank and the angular velocity given by cadence using the following equation: